2014
DOI: 10.1002/j.1532-2149.2014.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute abdominal pain in the emergency room: A systematic review of the literature

Abstract: Appropriate pain therapy prior to diagnosis in patients with acute abdominal pain remains controversial. Several recent studies have demonstrated that pain therapy does not negatively influence either the diagnosis or subsequent treatment of these patients; however, current practice patterns continue to favour withholding pain medication prior to diagnosis and surgical treatment decision. Populations; and (6) Ethical and Medico-legal Considerations in Current Analgesia Practices. A comprehensive algorithm for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 78 publications
(105 reference statements)
0
34
0
7
Order By: Relevance
“…A recent literature review in adults highlighted a lack of therapeutic consensus and an ongoing practice pattern that favors withholding analgesia prior to surgical evaluation. 11 Another recent study of children with appendicitis revealed that almost 60% did not receive analgesia. 12 Significant delays in time to analgesia have also been identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent literature review in adults highlighted a lack of therapeutic consensus and an ongoing practice pattern that favors withholding analgesia prior to surgical evaluation. 11 Another recent study of children with appendicitis revealed that almost 60% did not receive analgesia. 12 Significant delays in time to analgesia have also been identified.…”
mentioning
confidence: 99%
“…16,17 A recent retrospective chart review revealed that significantly fewer children with appendicitis are provided with analgesia compared to adults. 11 Suboptimal analgesia for abdominal pain appears to persist in children as evidenced a Canadian survey, which reported that only half of children being investigated for appendicitis received analgesia in the ED. 17 The highest rate of analgesia administration reported for acute abdominal pain in a pediatric ED setting was in Australia and New Zealand and only reached 62%.…”
mentioning
confidence: 99%
“…Historically, the reluctance among clinicians to provide analgesia to patients with acute abdominal pain 12,28,29 was thought to be due to concerns of obscuring the diagnosis of appendicitis, 30,31 leading to a delay in surgical management. 32,33 In a number of previous surveys of emergency physicians 23,28 and surgeons 19 , a large proportion of respondents chose not to provide analgesia until after surgical consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Dans notre étude, ces DANS représentaient 41 % des diagnostics de sortie inscrits sur les dossiers médicaux. Ce résultat est en accord avec les données de la littérature où les DANS ont une prévalence entre 19 % à 41 % selon les séries [2,7,8,16,20,26,27]. Dans notre étude, les DANS n'étaient pas significativement associés à une chronicisation des douleurs.…”
Section: Discussionunclassified